Snell's equity (Sweet & Maxwell, 2006)
Snell" deals with equitable principles and remedies, together with their application in trusts, probate and mortgages. Containing comprehensive coverage in this area, it offers expert interpretation of the rules of equity and how they can be applied in different situations. Th is 30th edition includes: examination of the nature of equities and the maxims of equity; discussion of dealings with equities including assignments of choses in action, and priorities; detailed coverage of the three main substantative fields of equity jurisdiction, namely trusts, the administration of assets, and securities, particularly mortgages; analysis of the five ancient equitable doctrines of conversion, reconversion, election, performance and satisfaction; individual assessment of the situations in which equity has intervened to safeguard those who, by their status or their circumstances, are in need of protection; and consideration of a wide range of equitable remedies.